Longitudinal Study of Credit Union Research: From Credit-Provision to Cooperative Principles, the Urban Economy and Gender Issues - Carlos Gabriel Parrales Choez; María del Carmen Valls Martínez; Pedro Antonio Martín-Cervantes (Complexity)
Credit unions are one of the most widely established corporate entities in the financial systems of most of the world’s nations. Their historical support to the financing needs of small savers, as well as their assimilation into the framework of contemporary microfinance, gives them an important specific weight in the economic-financial literature of our time. In this sense, our research has carried out a systematic review of the main contributions (articles in scientific journals) focused on the area of credit unions over the period 1936–2020, using Scopus and WoS as bibliographic databases. In summary, the main countries, journals, authors, articles, and the main collaborative research networks at the level of authors or countries have been analyzed. In the same way, the implementation of strategic diagrams based on Callon’s procedure has facilitated the classification of the most important terms linked to financial cooperativism, which has served to detect future lines of research related to the terms (among others): asymmetric-information, capital-provision, cooperative-principles, customer-reduction, gender-issues, neoinstitutionalism, poverty, and urban-economy.